The European Union Humanitarian Diplomacy Used as a Soft Power in the Middle East and Turkey - Tilovska-Kechedji, Elena; Rakitovan, Darian (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The European Union has always been practising good diplomatic and neighbouring relations with the Middle East and Turkey, but with the outbreak of the Syrian war and the enormous inflows of refugees on its continent, the EU is trying to use humanitarian diplomacy to protect itself, but also to help the Middle East and Turkey. The EU is using humanitarian diplomacy as a soft-power tool to balance and stabilise conflict-ridden, vulnerable situations. Humanitarian diplomacy is used for the purpose to protect and find solutions by methods of negotiations and relief for refugees, migrants and other vulnerable categories of people. It is persuading decision makers to act in the interests of the refugees and vulnerable groups with respect for human rights, and it derives from traditional diplomacy, which deals with specific activities in war and peace, and government functions. The main difference between the two is that humanitarian diplomacy does not use military and political tools, although it is influenced by them. The common ground is international human rights law and respect for human rights and principles. The EU's humanitarian diplomacy has not lost its sense of strategy, influence, and power, and it is able to meet the moral, political, and international directives to address and protect the human rights of all.